Intermedia in Ekosdance Company’s Garda the Musical: A Dick Higgins Perspective - Adi Wibowo; Tafsir Hudha (Creativity And Research Theatre Journal, 2026)
Ekosdance Company’s Garda the Musical brings together the actors’ bodies, choreography, music, lighting, digital animation, and stage space within an intermedia dramatic construction. This study examines the dramatic function of each medium, the relationships among media, and their effects on performance coherence. It employs a qualitative case-study design using performance videos and photographs, production archives, and interviews with artists and the creative team. The data were analyzed by categorizing media functions and scene structures through Dick Higgins’s concept of intermedia and George R. Kernodle’s dramatic anatomy, followed by source triangulation. The findings show that the integration of bodies, choreography, music, lighting, and digital animation creates synergies that reinforce exposition, conflict development, climax, and resolution while producing an aesthetic experience unattainable through a single medium. However, media density in several scenes leads to functional overlap, shifts in dramatic focus, and the risk of narrative fragmentation. These findings indicate that intermedia effectiveness does not depend on absolute equality among media but on a contextual hierarchy of dramaturgical functions that enables visual and auditory richness to support the actors’ bodies and narrative clarity.